Immobilization of Lead by Phosphated Biochar Produced from Fish Farming Sludge and Sewage Sludge in a Contaminated Urban Soil - Toledo, L.A. Bravo-; Vega, S.A. Castelo; Milla, D. E. Apeña; Contreras, A. Borda; Ramos, C.O. Tome-; Pisfil, J.A. Montaño; Miranda, B.C.L. Montaño; Farfán, R.E. Solís (International Journal of Membrane Science and Technology, 2023)
An evaluation was conducted on the application of phosphate biochar produced from Sewage Sludge (SS) of a Wastewater Treatment Plant (WWTP) for lead immobilization in contaminated soils of the Human Settlement (HS) Virgin of Guadalupe, in the district of Mi Peru. Biochar was generated by a slow pyrolysis process at 500°C. The biochar was dosed at 10% biochar/soil on lead-contaminated soil, and the factors studied were the type of biochar and time of application. A complete factorial design was performed, and the data were processed using Design Expert v11 software. The results showed that the maximum lead immobilization was 50.83% for BSS for 20 days at a dose of 10% biochar/soil. According to the factorial model, an R² of 0.85, an adjusted R² of 0.83, an F-value of 79.64, and p-values lower than 0.05 (95%) were obtained, indicating that the factor (F2) of application time is significant for the treatment. It was concluded that both types of sludge have the potential for lead immobilization in contaminated soil, and the application time is significant for lead immobilization.